2006
DOI: 10.1111/j.1365-2133.2005.07082.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of childhood eczema and asthma on parental sleep and well-being: a prospective comparative study

Abstract: Compared with looking after a child with chronic asthma, caring for a child with chronic atopic eczema was associated with greater parental sleep disturbances. Disruption to parental sleep correlated with anxiety levels and, in the case of mothers, depression scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 19 publications
(18 reference statements)
2
113
3
4
Order By: Relevance
“…Disturbed sleep for parents and AD sufferers because of nighttime itching exacerbated other problems; one study found sleep diffi culties at some point in up to 60% of children with AD [ 39 ]. Moore et al [ 40 ] demonstrated a direct correlation between severity of sleep disturbance and maternal anxiety and depression scores, and paternal anxiety scores.…”
Section: How Does Ad Affect Stress Levels and Well-being?mentioning
confidence: 97%
“…Disturbed sleep for parents and AD sufferers because of nighttime itching exacerbated other problems; one study found sleep diffi culties at some point in up to 60% of children with AD [ 39 ]. Moore et al [ 40 ] demonstrated a direct correlation between severity of sleep disturbance and maternal anxiety and depression scores, and paternal anxiety scores.…”
Section: How Does Ad Affect Stress Levels and Well-being?mentioning
confidence: 97%
“…In fact, the depression rate in mothers of children with AD is twice as high as in mothers of children with asthma. 16 Appropriate social and community support resources, such as referral to a counselor, psychologist, or patient support groups, such as the National Eczema Association (www.nationaleczema. org), can be helpful when QoL issues are encountered in patients and families with AD.…”
Section: Effects On Quality Of Lifementioning
confidence: 99%
“…The age of children and whether they live with one or both parents influenced the outcomes. Sleeping disorder was also associated with anxiety and depression (21). Results from three studies showed that sleep disorder in parents of children with chronic diseases such as asthma and cystic fibrosis correlated with depression, anxiety, happiness and marital life.…”
Section: Discussionmentioning
confidence: 97%